1996
DOI: 10.1103/physrevlett.76.1982
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Correlation in Quantum Chaotic Systems with Time-Reversal Symmetry: Theory and Experiment

Abstract: The correct Eqs. (20) and (21) read as follows:Q ab cdQ1982 0031-9007͞96͞76(11)͞1982(1)$10.00

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…An overwhelming number of numerical experiments on spectral statistics [3,4] and their corresponding semiclassical analysis [5,6] suggest that the universal features observed in chaotic quantum systems can be modelled in terms of random matrix theory. Apart from energy spectra, it has been found that the conjecture [7] where an eigenstate of a chaotic quantum system is represented as a Gaussian random superposition of plane waves entails results which are found in agreement with numerical studies [8,4]. We believe that an important step has been in establishing the result that this conjecture leads to momentum distribution of ideal gases, thus bringing out statistical mechanics [9].…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…An overwhelming number of numerical experiments on spectral statistics [3,4] and their corresponding semiclassical analysis [5,6] suggest that the universal features observed in chaotic quantum systems can be modelled in terms of random matrix theory. Apart from energy spectra, it has been found that the conjecture [7] where an eigenstate of a chaotic quantum system is represented as a Gaussian random superposition of plane waves entails results which are found in agreement with numerical studies [8,4]. We believe that an important step has been in establishing the result that this conjecture leads to momentum distribution of ideal gases, thus bringing out statistical mechanics [9].…”
Section: Introductionsupporting
confidence: 77%
“…As noted in [9], the higher-order even-point correlation functions factorize and the odd-ones vanish. A very important aspect of the ansatz (7), (8) is that the…”
Section: Momentum Distributionmentioning
confidence: 99%
See 1 more Smart Citation